SIMULATIONS OF PROCESSORS FOR FORMING ANDDIGITAL SIGNAL PROCESSING IN COMPUTER SYSTEMS WITH OPEN OPTICAL CHANNELS - Grynchyshyn, Taras; Nykolaychuk, Yaroslav (International Journal of Computing, 2014)
In this article new methodology of unsurplus signals code of bit-oriented informative streams is offered with the use of codes of the field of Galois, that considerably optimizes and improves the known methods of the digital working of data with an exposure and correction of errors, and effectively realized on the basis of the offered structures of the special processors of digital treatment of signals.